Trauma care in emergency situations: Organisation of medical response and local community resilience - Matejić, Tomislav; Kaštelan, Snježana; Lovrić, Ivana; Kaštelan Brumen, Uršula; Car, Anja (Crisis Management Days, 2025)
Emergencies such as natural disasters, industrial accidents, and mass trauma events demand a rapid, coordinated medical response to minimise morbidity and mortality. Effective trauma care hinges on structured protocols, accurate triage, resource optimisation, and interdisciplinary collaboration. Triage systems, including the Advanced Trauma Life Support (ATLS) protocol and Simple Triage and Rapid Treatment (START), prioritise patients based on injury severity, ensuring timely intervention. Haemorrhage control with tourniquets, and haemostatic dressings is critical for survival. Immediate access to diagnostic imaging, point-of-care testing and early blood transfusions enhance outcomes. Hospital emergency plans must account for surge capacity, patient diversion, and intensive care unit preparedness. Trauma centres should implement damage control strategies, including resuscitative thoracotomy and early goal-directed therapy. The integration of telemedicine allows specialists to provide real-time guidance, improving diagnostic accuracy and treatment efficiency. Artificial intelligence (AI) and digital health tools enhance emergency response by optimising triage, predicting patient deterioration, and streamlining workflows. Cloud-based electronic health records and geographic information systems facilitate real-time data sharing and rapid deployment of medical teams. Lessons from past crises highlight the need for systematic training, simulation exercises, and multi-agency collaboration. Disaster medicine courses equip healthcare providers with essential trauma management skills, and regular disaster drills strengthen healthcare system resilience and preparedness. Sustainable emergency care requires adaptable response models, continuous resource monitoring, and refinement of strategies based on evidence-based practices. Investment in healthcare infrastructure, including trauma centres, mobile field hospitals, and helicopter emergency medical services is crucial for managing large-scale emergencies. In conclusion, timely emergency trauma care depends on well-coordinated medical responses, advanced technologies, and continuous training. Strengthening local community resilience through systematic preparedness is essential for mitigating the impact of future crises and safeguarding public health.